The Princeton Encyclopedia of Poetry and Poetics : Fourth Edition - Slessarev, Alexandra; Marno, David; Feinsod, Harris; Rouzer, Paul F.; Ramazani, Jahan, 1960-; Cavanagh, Clare; Cushman, Stephen, 1956-; Greene, Roland, 1957- (Book collections on Project MUSE., 2012)
Provides the most comprehensive and authoritative reference for students, scholars, and poets on all aspects of its subject including history, movements, genres, prosody, rhetorical devices, and critical terms. This edition reflects recent changes in literary and cultural studies, providing up-to-date coverage and giving greater attention to the international aspects of poetry.